The Federal Democratic Republic of Ethiopia : 2008 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for The Federal Democratic Republic of Ethiopia. (IMF Staff Country Reports; Country Report, 2008)
This 2008 Article IV Consultation highlights that the Ethiopian economy has been growing rapidly in the last four years. Favorable weather conditions and pro-growth policies have helped sustain recovery from a sharp drought-related contraction in 2002/03. Growth has averaged 11 percent since 2003/04, far exceeding the minimum growth target of 7 percent in the Program for Accelerated and Sustainable Development. The rise in world oil prices has significantly added to pressures on international reserves. Surging coffee prices have helped to limit the impact on the terms of trade.